Evaluasi Preseptor Lapangan Pada Kegiatan Kepaniteraan Klinik Mahasiswa Prodi Pendidikan Profesi Bidan FK UNAND - Hindun Mila Hudzaifah; Feri Anita Wijayanti; Rafika Oktova; Laila Rahmi (Cetta: Jurnal Ilmu Pendidikan, 2023)
The Quality Control Group of Midwife Professional Study Program makes maximum efforts in carrying out its main tasks and functions as well as quality control in every lesson in the study program. The obstacle faced is the absence of clinical clerkship evaluation activities by field preceptors on the learning process carried out in study programs through relevant measuring instruments in the form of questionnaires. The purpose research is to create   documented, can be analyzed and followed up As an effort to improve and improve sustainable quality. Type of research is cross-sectional approach. This study used total sampling with respondents from all field preceptors in the practice area of ​​the Health Center, Independent Midwife Practice and network hospitals in the Midwife Professional Education Study Program with a total of 21 respondents. The results of the validity test on the research questionnaire items were 0.001 so all questionnaire items were declared valid. The results of the questionnaire reliability test were > 0.8 so the reliability was very good. The results of average value of the field preceptor on the assessment of the application of the theory are 84.69%, and the assessment of lecturer and student interactions is 78.91%. Furthermore, the assessment of the preparation for clinical clerkship activities was 88.10% the assessment of students regarding clinical clerkship activities was 75.89%. The results of the overall assessment are categorized as very good so that they can be used as a reference for improving the quality of learning.